2013
DOI: 10.1111/codi.12281
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of concomitant chemoradiotherapy with local hyperthermia and metronidazole for locally advanced fixed rectal cancer

Abstract: Aim Locally advanced fixed T4 rectal cancer has a poor prognosis and no standard treatment strategy. The aim of this study was to investigate the safety and efficacy of neoadjuvant chemoradiotherapy using hypofractionated radiotherapy combined with local hyperthermia, capecitabine, oxaliplatin and metronidazole.Method Radiotherapy was given to a total dose of 40 Gy in 10 fractions. Capecitabine 650 mg/m 2 twice a day was given on days 1À22 and intravenous oxaliplatin 50 mg/m 2 was administered on days 3, 10 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…A recent prospective phase II study applied a quadrimodal preoperative regimen for locally advanced fixed (T4) rectal cancers. Treatment consisted of hypofractionated radiotherapy with concomitant capecitabine and oxaliplatin, rectal metronidazole and capacitative hyperthermia with a target temperature of 41-45 C. The authors report a complete resection rate of 92% and a local failure rate of 13.6% after a median follow-up of 24.9 months [19]. These numbers are superior to data reported before for this population with a very high risk for local failure [20].…”
Section: Discussionmentioning
confidence: 73%
“…A recent prospective phase II study applied a quadrimodal preoperative regimen for locally advanced fixed (T4) rectal cancers. Treatment consisted of hypofractionated radiotherapy with concomitant capecitabine and oxaliplatin, rectal metronidazole and capacitative hyperthermia with a target temperature of 41-45 C. The authors report a complete resection rate of 92% and a local failure rate of 13.6% after a median follow-up of 24.9 months [19]. These numbers are superior to data reported before for this population with a very high risk for local failure [20].…”
Section: Discussionmentioning
confidence: 73%
“…In a further retrospective study encompassing 235 patients, HT appeared to confer better downstaging of the primary tumor and involved lymph nodes (95). Two small studies evaluated hypofractionated RTHTCT schemes showing principal efficacy and safety (96, 97). Additional HT appears to be well tolerated without increased impairment of quality of life (98).…”
Section: Clinical Evidence Of Combined Thermoradiotherapymentioning
confidence: 99%
“…In a retrospective review of 106 patients, Schroeder et al found that patients treated with the addition of regional hyperthermia had improved pCR rates (16.4% versus 6.7%) 40. However, two single-group Phase II studies combining hyperthermia with nCRT found similar pCR compared with nCRT alone 41,42. Therefore, the role of hyperthermia is unclear.…”
Section: Efforts To Improve the Efficacy Of Ncrtmentioning
confidence: 99%